Spore Evidence for the Origin of Isoetalean Lycopsids? - Jiří Bek; Jana Votočková Frojdová (Life, 2023)
A new hypothesis about the origin of isoetalean lycopsids was proposed based on palynological data. The occurrence of three apical papillae on the proximal surfaces of miospores is a significant palynological feature that is clearly defined in both isoetalean and selaginellalean clades. Three apical papillae appeared for the first time within lower Silurian (Wenlockian ca. 430 My) and only in rhyniophytoid plants. Using this observation, we suggest that isoetalean lycopsids could have evolved directly from rhyniophytoids and not from protolepidodendralean lycopsids in the middle Devonian (Eifelian–Givetian) as previously suggested, because protolepidodendralean spores do not possess three apical papillae. Spores with three apical papillae, reported as dispersed as well as in situ, were recorded continuously from the lower Silurian (Wenlockian) through the Devonian, Carboniferous, Permian, Mesozoic to Cenozoic era and form a phylogenetically independent lineage.